Anlotinib combined with penpulimab in the treatment of advanced adult thoracic spinal osteosarcoma: a case report - Chen, Xiaochun; Li, Xianqin; Zhao, Haiying; Qu, Jinwen; Li, Xiaojuan; Lin, Chuan; Yuan, Zhiping (Frontiers in Pharmacology, 2025)
BackgroundSpinal osteosarcoma is a rare and prognostically poor subtype of osteosarcoma, with limited efficacy from traditional chemoradiotherapy. The potential of targeted therapy combined with immunotherapy requires further exploration.Case SummaryA 53-year-old female with stage IV thoracic spinal osteosarcoma initially received intensity-modulated radiotherapy (total dose of 45 Gy in 15 fractions) and AP chemotherapy (doxorubicin 60 mg/m2 + cisplatin 100 mg/m2). Treatment was discontinued due to grade 4 myelosuppression and sepsis. Subsequently, concurrent combination therapy with anlotinib (12 mg daily for 14 days followed by a 7-day rest) and penpulimab (200 mg intravenously every 3 weeks) was initiated. Penpulimab was administered regularly for 2 years before discontinuation, while anlotinib was reduced to 10 mg daily due to grade 2 hand-foot syndrome and continued thereafter. Post-treatment, the patient achieved significant pain relief, restored self-care capacity, and stable disease (SD) with a progression-free survival (PFS) exceeding 33 months.LessonsThis case demonstrates that sequential molecular targeted therapy and immunotherapy following chemoradiation can yield remarkable clinical outcomes, offering a novel therapeutic option for advanced spinal osteosarcoma. However, interindividual variations in treatment response underscore the need for future research to identify predictive biomarkers for patient stratification.